(untitled) (Texas Journal of Medical Science, 2023)
Compressive myelopathy is a neurological deficit that results from compression of the spinal cord and leads to a variety of symptoms and potentially serious consequences. Magnetic resonance imaging (MRI) is the gold standard for diagnosing compressive myelopathy as it provides high-resolution anatomical images and is the preferred method for evaluating the underlying pathology, but somatosensory evoked potentials (SSEPs) have also been used as a diagnostic tool as it provides information about the functional integrity of the spinal cord and assess the severity and extent of the damage. This article presents a comparative analysis of MRI and SSEPs in the diagnosis of compressive myelopathy and discusses the complementary role they can play in diagnosis and monitoring of the disease. Seventy four subjects were involved in the study, divided into controls (35) and cases (39) of myelopathies due to disc herniation. Severity of myelopathy for cases group were classified according to modified Japanese Assessment scale (mJOA) into; mild, moderate and severe. SSEPs showed more correlation with severity of myelopathy more than MRI (r=0.948, 0.599 respectively) and higher sensitivity of SSEPs for detecting severe myelopathies (91.7%) while MRI sensitivity was only (16.7%) sensitive.